2019
DOI: 10.3390/foods8060218
|View full text |Cite
|
Sign up to set email alerts
|

Use of Selected Lactobacilli to Increase γ-Aminobutyric Acid (GABA) Content in Sourdough Bread Enriched with Amaranth Flour

Abstract: γ-Aminobutyric acid (GABA) is the primary inhibitory neurotransmitter of the central nervous system and possesses various physiological functions. GABA production can be obtained thanks to lactic acid bacteria activity in different foods such as sourdoughs. Recently, breads made from blends of pseudocereals and wheat flours have attracted much attention. Amaranth is especially interesting because of its high nutritional value, having a high protein content and containing different antioxidant compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 53 publications
2
17
1
Order By: Relevance
“…Lactis was able to increase the GABA amount in fried sourdough bread (bhatura, an Indian traditional fermented food) [74]. L. farciminis and L. brevis species were also able to increase GABA content during sourdough fermentation and improved the GABA content of the final baked goods [75]. The ability of Lactobacillus plantarum ATCC 8014 to increase GABA content in quinoa sourdough and the final baked muffins was also shown in our previous study [27].…”
Section: Amino-acids Content Of Final Baked Muffinssupporting
confidence: 57%
“…Lactis was able to increase the GABA amount in fried sourdough bread (bhatura, an Indian traditional fermented food) [74]. L. farciminis and L. brevis species were also able to increase GABA content during sourdough fermentation and improved the GABA content of the final baked goods [75]. The ability of Lactobacillus plantarum ATCC 8014 to increase GABA content in quinoa sourdough and the final baked muffins was also shown in our previous study [27].…”
Section: Amino-acids Content Of Final Baked Muffinssupporting
confidence: 57%
“…The greatest interest has recently been gained by amaranth seeds flour, the raw material for which production is the plant "Amaránthus" -the oldest grain crop, which is the main source of protein up to 35% (including essential amino acids), easily digestible by the human body [4][5][6][7]. Figure 1 shows the chemical composition and nutritional value of amaranth seed flour, %…”
Section: Introductionmentioning
confidence: 99%
“…This favours both intestinal regularity and weight control. Moreover, previous research has reported a higher antioxidant activity and an increased content of total phenolic compounds in breads enriched with amaranth flour [73].…”
Section: Discussionmentioning
confidence: 87%